Particle UZHE [already] and Methods of its Translation into Vietnamese - I. N. Tokarchuk; A. Yu. Erysheva (Научный диалог, 2020)
The problem of the translation of Russian particles into foreign languages is considered on the example of one of the most frequent inter-style units - word already . The variety of semantic-pragmatic manifestations of this particle in the utterance and text is shown; the resulting discrepancies in interpretation are already described in dictionaries and research papers. A classification of typical uses of already is proposed, including twelve semantic-syntactic variants of a particle, distinguished depending on the nature of compatibility with syntactic components and the semantics inherent in these uses. A connection is established between the types of particle use based on a number of invariant semantic components, the main of which are ‘change of situation’, ‘expectation’, ‘earlier than expected’, ‘late / later’, ‘many / more’, ‘little / less’, ‘long’. Based on the material of M. A. Bulgakov’s story “Fatal Eggs” and the text of its translation into Vietnamese, the typical semantic-pragmatic realizations of the particle already are analyzed and the features of the methods used to translate sentences with this particle are determined. It has been established that the most popular means of direct translation (75% of the total number of uses) is the functional word đã , less often the combination đã ... rồi is used - in the case of the transfer of meanings of already the ‘expected change in the situation’, ‘many’, ‘long’, ‘late’, as well as the combination of không còn ... nữa - no longer with the meaning ‘expected change of situation to the opposite’.